Documenti probatori presentati da Ferdinando d’Asburgo nell’inchiesta per l’uccisione di Frate Giorgio Martinuzzi Utyeszenics (1551) - Papo, Adriano; Nemeth, Gizella (Études sur la Région Méditerranéenne, 2021)
Immediately after the killing of Friar George Martinuzzi Utyeszenics, which took place on 21 December 1551, the king of the Romans and of Hungary, Ferdinand I of Habsburg, took action to organize his defense and that of his accomplices in view of the investigation that Pope Julius III was about to call to judge the offenders of killing the friar, who was also a cardinal. Ferdinand produced through his lawyers a series of evidences that would bring to light the serious faults of George Martinuzzi, which, if not revealed in time, would bring Hungary and the whole of Christianity to ruin. About fifty documents were attached to the tests, some of which (for example, Martinuzzi’s letters to the sultan and the various Turkish pashas) were overwhelming evidence that proved the friar’s connivance with the Turks.